PENGARUH RASIO KEUANGAN DAN FAKTOR FUNDAMENTAL EKONOMI MAKRO TERHADAP KINERJA KEUANGAN BANK BUMN DI INDONESIA - Febriani, Komang; I Gusti Ayu Purnamawati (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to analyze the effect of financial ratios and macro fundamental factors on the financial performance of state-owned banks in Indonesia. This study uses quantitative methods with secondary data from the financial statements of each state-owned bank (BRI, BNI, BTN, Mandiri) and macroeconomic data from the Central Bureau of Statistics and BI for the 2019-2023 period. The number of samples obtained was 160 observation data, which came from 4 banks over a 5-year period by considering observations of several research variables such as financial ratios (ROA, LDR, NPL, CIR) and macroeconomic fundamental indicators (Inflation, Interest Rates, Exchange Rates) each year. The data were analyzed using multiple linear regression and classical assumption tests. The results showed that ROA, LDR, NPL, and Exchange Rate showed a positive but insignificant influence on the financial performance of state-owned banks. CIR, Inflation, and Interest rates show a negative but insignificant influence on the financial performance of state-owned banks.